Proteomic Analysis of Potential Keratan Sulfate, Chondroitin Sulfate A, and Hyaluronic Acid Molecular Interactions - Conrad, Abigail H.; Zhang, Yuntao; Tasheva, Elena S.; Conrad, Gary W. (My University, 2009)
Purpose: Corneal stroma extracellular matrix (ECM) glycosaminoglycans (GAGs) include keratan sulfate (KS), chondroitin sulfate A (CSA), and hyaluronic acid (HA). Embryonic corneal keratocytes and sensory nerve fibers grow and differentiate according to chemical cues they receive from their ECM. This study asks what proteins that might regulate keratocytes or corneal nerve growth cone immigration interact with corneal GAGs. Method: Biotinylated KS (bKS), CSA (bCSA), and HA (bHA) were prepared, and used in Invitrogen’s v4 protoarray to assess their interactions with 8268 proteins and a custom array of 85 extracellular epitopes of nerve growth-related proteins. Surface Plasmon Resonance (SPR) was performed with bKS and SLIT2, and their Ka, Kd, and KD values determined. Results: Highly sulfated KS interacted with 217 v4 proteins, including 75 kinases, several membrane or secreted proteins, many cytoskeletal proteins, and many nerve function proteins. CSA interacted with 24 v4 proteins, including 10 kinases and 2 cell surface proteins. HA interacted with 6 v4 proteins, including several ECM-related structural proteins. Of 85 ECM nerve-related epitopes, KS bound 40 proteins, including SLIT, 2 ROBOs, 9 EPHs, 8 Ephrins (EFNs), 8 semaphorins (SEMAs) and 2 nerve growth factor receptors. CSA bound 9 proteins, including ROBO2, 2 EPHs, 1 EFN, 2 SEMAs, and Netrin4. HA bound no ECM nerve-related epitopes. SPR confirmed that KS binds SLIT2 strongly. KS core protein mimecan/osteoglycin bound 15 v4 proteins. Conclusion: Corneal stromal GAGs bind, and thus could alter the availability or conformation of, many proteins that may influence keratocyte behavior and nerve growth cone behavior in the cornea.
Published April 7, 2010 as a Recently Accepted Papers (RAPpers)
Keywords: Invitrogen v4 ProtoArray Protein List; Glycosaminoglycans; Proteomics microarray; Keratan sulfate; Cornea; Extracellular matrix; Glycomics microarray